Work-in-Progress-Design Method of a Real-Time Monitoring System for ICT Evaluation Process in Education Based on CesiumJS 3D Visualization - Wu, Chen; Chen, Meng; Wu, Di; Ma, Jiman; Xu, Jian; Ma, Binbin (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
ICT (information and communications technology) evaluation in education is a key step in measuring the development level of education informatization. At present, the statistical data of evaluation process mainly be transmitted in the form of static chart files. How to grasp the overall evaluation status of each evaluation area in real time and understand the latest progress and bottlenecks of evaluation work is an urgent problem. This work-in-progress paper proposes a real-time monitoring system for ICT evaluation process in education based on CesiumJS 3D visualization, which can provide multi-modal 3D visualization for dynamic evaluation process data and further support knowledge mining.